Investigation of a possible association of potentially inappropriate medication for older adults and frailty in a prospective cohort study from Germany - Laetsch, Dana Clarissa; Hoppe, Liesa Katharina; Saum, Kai-Uwe; Haefeli, Walter E.; Brenner, Hermann; Schöttker, Ben (Age & ageing, 2020)
Objective: potentially inappropriate medications (PIMs) are commonly defined as drugs that should be avoided in older adults because they are considered to have a negative risk-benefit ratio. PIMs are suspected to increase the risk for frailty, but this has yet to be examined. Design: prospective population-based cohort study. Setting and participants: a German cohort of community-dwelling older adults (>= 60 years) was followed from October 2008 to September 2016. Methods: in propensity score-adjusted logistic and Cox regression models, associations between baseline PIM use and prevalent/incident frailty were investigated. Frailty was assessed using the definition by Fried and co-workers, PIM were defined with the 2015 BEERS criteria, the BEERS criteria to avoid in cognitively impaired patients (BEERS dementia PIM), the EU(7)-PIM and the PRISCUS list. Results: of 2,865 participants, 261 were frail at baseline and 423 became frail during follow-up. Only BEERS dementia PIM use was statistically significantly associated with prevalent frailty (odds ratio (95% confidence interval), 1.51 (1.04-2.17)). The strength of the association was comparable for all frailty components. Similarly, in longitudinal analyses, only BEERS dementia PIM use was associated with incident frailty albeit not statistically significant (hazard ratio, 1.19 (0.84-1.68)). Conclusions: the association of PIM use and frailty seems to be restricted to drug classes, which can induce frailty symptoms (anticholinergics, benzodiazepines, z-substances and antipsychotics). Physicians are advised to perform frailty assessments before and after prescribing these drug classes to older patients and to reconsider treatment decisions in case of negative performance changes.
Published electronically 16 November 2019
Gesehen am 08.04.2020